From creation to chaos: Classic writings in science - Dixon, bernard (Oxford Basil Blackwell, 1989)
This anthology of the literature of science comprises a collection of English prose, and some poetry, which sets out to demolish the myth that scientists cannot write and science is difficult and dull. The pieces are by scientists both ancient and modern, from Charles Darwin to Richard Dawkins, Isaac Newton to Peter Medawar, William Gilbert to Primo Levi. Also included are writings by such scientifically-minded laymen as H.G.Wells, W.H.Hudson and Arthur Koestler.
Keywords: English literature; Nature of science; Philosophy of science